Influence of lipopolysaccharides on the attachment of Thiobacillus ferrooxidans to minerals - Escobar, Blanca (1997)
The loss of part of the lipopolysaccharides (LPS) of the outer membrane of T. ferrooxidans negatively in¯uenced the attachment of the bacteria to minerals and the bioleaching process. LPS previously extracted from T. ferrooxidans and which had come into contact with pyrite inhibited the attachment of cells to minerals and also negatively affected the bioleaching. These results suggest that LPS play an important role in the attachment of the microorganisms and therefore, its presence or absence could affect the bioleaching process.